Low‐altitude UAV air‐ground propagation channel measurement and analysis in a suburban environment at 3.9 GHz. Issue 9 (30th April 2019) - Cui, Zhuangzhuang; Briso, César; Guan, Ke; Matolak, David W.; Calvo‐Ramírez, César; Ai, Bo; Zhong, Zhangdui
Abstract : Unmanned aerial vehicles (UAVs) have been applied to various promising applications because of their features of high‐mobility, portability, rapid deployment, and modest power consumption. Small UAVs fly at low altitudes and typically short distances from the ground controller. It is of interest and value to model the propagation channel between low‐altitude UAVs and ground stations. This article presents results of channel measurements at 3.9 GHz carried out in a suburban environment with a small‐size UAV flying at low altitudes, up to 40 m. The authors also present comparative results from ray‐tracing simulations. Height‐dependent models for path loss, root mean square (RMS) delay spread, and the number of multipath components are provided. The results illustrate that although multipath effects exist at low altitudes in this environment, the two‐ray path loss model works reasonably well in describing the channel behaviour. Initial ray tracing simulations show reasonable agreement with measurements. In addition, RMS delay spread results indicate that distant scatterers have an appreciable effect on the UAV air‐ground (AG) propagation channels, which can be different from some terrestrial channels. Authors' results should be of use in the modelling of low‐altitude AG propagation channels and in the performance analysis of UAV‐enabled AG communication systems.